Peripheral Signals Mediate the Beneficial Effects of Gastric Surgery in Obesity - Silvia Barja-Fernández; Cintia Folgueira; Cecilia Castelao; Rosaura Leis; Felipe F. Casanueva; Luisa M. Seoane (Gastroenterology Research and Practice)
Obesity is nowadays a public health problem both in the industrialized world and developing countries. The different treatments to fight against obesity are not very successful with the exception of gastric surgery. The mechanism behind the achievement of this procedure remains unclear although the modifications in the pattern of gastrointestinal hormones production appear to be responsible for the beneficial effect. The gastrointestinal tract has emerged in the last time as an endocrine organ in charge of response to the different stimulus related to nutritional status by the modulation of more than 30 signals acting at central level to modulate food intake and body weight. The production of some of these gastric derived signals has been proved to be altered in obesity (ghrelin, CCK, and GLP-1). In fact, bariatric surgery modifies the production of both gastrointestinal and adipose tissue peripheral signals beyond the gut microbiota composition. Through this paper the main peripheral signals altered in obesity will be reviewed together with their modifications after bariatric surgery.